Phosphonated Polyethylenimine‐Coated Nanoparticles: Size‐ and Zeta‐Potential‐Adjustable Nanomaterials. (23rd August 2013) - Monteil, Clément; Bar, Nathalie; Moreau, Bernard; Retoux, Richard; Bee, Agnès; Talbot, Delphine; Villemin, Didier
<x xml:space="preserve">Abstract</x> Novel partially phosphonated polyethylenimine polymers are developed in order to control the modification of nanoparticle (NP) surfaces. This polymer is built by an accessible one‐step process. The numerous phosphonate functions assume both a strong covalent anchoring on metal oxide NPs and a modulation of electric charges, while amino groups are associated with dispersion preservation and subsequent biofunctionalization. The zwitterionic nanomaterials obtained display a good stability toward pH and ionic strength. According to the selected percentage of phosphonation and the polymer size, zeta potential, and diameter of the particles are controlled.